Evaluasi Beban Belajar pada Kurikulum 2013 untuk Mata Pelajaran PAI di SMP/MTs - Amanda Hotija; Tiara Hartanti; M. Mahbubi (Jurnal Teologi Islam, 2025)
This study aims to evaluate the learning load in the PAI subject, focusing on the number of lesson hours, the material taught, and the level of difficulty faced by students. The research method used is a qualitative approach with data analysis through interviews with PAI teachers, classroom observations, and document studies related to the curriculum and teaching materials. The results of the study indicate that the learning load in PAI at SMP/MTs is still perceived as heavy by some students, particularly in understanding material that is considered abstract and requires additional time for comprehension. Therefore, it is recommended to make adjustments in lesson planning and material preparation to better match students' capacity, as well as consider more flexible time durations without compromising the quality of learning. Continuous evaluation is necessary to improve the implementation of a more effective curriculum.